English Teacher’s Employment of Code-Switching in EFL Classroom: Types and Functions - Aleksius, Madar (LPPM STKIP Kusuma Negara, 2024)
Code-switching in the teaching and learning process is a natural phenomenon, meaning the teacher changes the language during the teaching and learning process, either from Indonesian to English or vice versa. The current study was intended to discover the types and functions of code-switching used by English teachers in classroom interaction. This type of research is qualitative. The subject of the study is an English teacher who teaches English in Grade 11 at a private high school in Kupang, Indonesia. The research data were collected through class observation and recording of the teacher’s utterances during the teaching-learning process. The study uncovers three types of code-switching i.e.: tag switching, inter-sentential, code-switching, and intra-sentential code-switching. Of the three types, intra-sentential code-switching was the most dominantly used by the teacher. The study also found the functions of code-switching used by the teacher in classroom teaching namely repetition, explanation, asking, and translation. The most dominant function of code-switching used by the teacher was translation. It is recommended that English teachers may employ code-switching in learning activities according to the needs and the level of ability of the students. By doing code-switching, the learning process can run smoothly, and the desired goals can be achieved.